Processing : creative coding and computational art - Greenberg, Ira (Friends of Ed, an Apress Co., 2007)
"This book is written especially for artists, designers, and other creative professionals and students exploring code art. The book provides a solid and comprehensive foundation in programming, including object-oriented principles, and introduces the reader to the easy-to-grasp Processing language."--Jacket